DEVELOPMENT OF INDONESIAN ANTI AIRCRAFT ARTILLERY UNITS IN THE FRAMEWORK OF NATIONAL AIR DEFENSE IN THE ERA OF MODERN WAR - Roza, Hendra; Kustiawan, Bambang; Handoko, Tri (Jurnal Governansi, 2024)
The current dynamics of war, which is increasingly influenced by increasingly rapid technological advances, demands adaptation and innovation in the defense and security strategy of a sovereign country. Reflecting on the Russia-Ukraine war, equipping each Rai Arhanud in each Battalion and Missile Unit is very strategic and very necessary. But currently, Arhanud TNI AD does not yet have an anti-drone unit that specifically handles the threat of enemy attacks spread throughout Kotama. This can affect our defense capabilities faced with the development of modern weapons of war. The research aims to analyze the integration of anti-drone technology into its operational structure and doctrine to increase the effectiveness and efficiency of air defense operations in the Indonesian Army Arhanud unit. The research method uses a descriptive method with a qualitative approach through the number of samples referring to the analysis of the TNI AD leadership. The results of the research show that the personnel or human resources of the TNI AD Arhanud Unit generally have adequate capabilities in carrying out the main tasks of air defense. Comprehensive adjustments are needed, both from an operational and tactical perspective, to integrate anti-drone technology into Arhanud’s unit. Arhanud’s unit has good readiness to face conventional threats, but currently they are still not equipped with a special anti-drone unit specifically designed to detect, track and neutralize enemy drone attacks. Greater encouragement and priority is needed to develop anti-drone technology to deal with increasingly complex air threats.